A public database on coffee agroforestry systems: construction and bibliometric analysis - López Sampson, Arlene; Orozco, Inyhalia; Aragón Murillo, Elizabeth; Jiménez Pérez, Jeffry (Springer, 2025)
Coffee production faces complex challenges that threaten the sustainability of the sector. Coffee agroforestry systems are widely recognized as a venue to deal with this interconnected environmental and socioeconomic challenges by enhancing the resilience of the agroecosystem through the promotion of ecological-based land practices. However, information on the benefits of associating trees with sustainability and other complex challenges remains scattered and often difficult to retrieve. This study aimed to build a comprehensive bibliographic database on coffee agroforestry systems containing pertinent and useful literature. Web of Science and the Agricultural Information and Documentation System of the Americas (SIDALC) and agroforestry expert local databases were consulted. A systematic search of publications related to coffee agroforestry systems was carried out for the last 60 years (1964–2024). Bibliometric methods were used to analyze the references. A total of 1317 references were included in the bibliographic database published in Zotero. For the bibliometric analysis, only 1107 references were considered. Latin America (702 publications) is the region with the highest number of publications on coffee agroforestry. The top 10 most frequent terms were: “agroforestry”, “agroecology”, “agroforestry systems”, “biodiversity”, “certification”, “climate change”, “ecosystem services”, “pest insects”, “shade”, and “sustainability”, with variations in use between years. Terms such as “climate change” and “biodiversity” have been a growing focus of research in the last five years of the period analyzed. The Centre de Coopération Internationale en Recherche Agronomique pour le Développement (Cirad), Universidade Federal de Lavras, and Universidade Federal de ViVosa were the institutions with the highest share of publications on coffee agroforestry systems. The bibliographic reference database offers an overview of research trends in coffee agroforestry and sheds light on key knowledge gaps that must be addressed to tackle some of the pressing challenges of the sector.